Generalizations of Hardy's integral inequalities - Yang Bicheng; Lokenath Debnath (International Journal of Mathematics and Mathematical Sciences)
This paper deals with some new generalizations of Hardy's integral inequalities. Some cases concerning whether the constant factors involved in these inequalities are best possible are discussed in some detail.